An unusual presentation of dental calculus - Venkateshwarapuram Rengaswami Balaji; Thanvir Mohammed Niazi; Manikandan Dhanasekaran (Wolters Kluwer Medknow Publications, 2019)
Calculus is a mineralized bacterial plaque that is formed on natural teeth surfaces where there is constant supply of saliva. Dental calculus is commonly seen over the buccal surfaces of maxillary molars and lingual surfaces of mandibular anterior teeth where the salivary duct opens into the oral cavity. This case report presents an unusual presentation of a large hard calcified mass in the left side of retromolar region associated with partially erupted tooth; hard mass was excised and examined histochemically which suggested the presence of calculus. Elimination of such nidus shall prevent formation of such calculus in such unusual position. This can also be achieved with proper oral hygiene measures.